Significance of platelet distribution width as a severity marker of erectile dysfunction. (15th July 2016) - Guo, L.Q.; Liu, Y.Q.; Sun, W.D.; Yuan, M.Z.; Xiao, Z.Y.; Song, H.B.; Zhao, S.T.; Zhang, X.L.; Ge, N.
Summary: Mean platelet volume (MPV) and Platelet distribution width (PDW) are potential markers in platelet activation. In present study, we aimed to evaluate MPV and PDW as potential severity markers for those patients who are complaining erectile dysfunction (ED). A total of 358 participants were enrolled in this study. The whole cohort was asked to complete the International Index of Erectile Function‐5 (IIEF‐5) questionnaire. The participants were classified into 3 groups: control group ( n  = 120), mild ED ( n  = 118) and severe ED ( n  = 120). We found in our cohort MPV and PDW were significantly higher in both mild ED group and severe ED group than control group (9.24 ± 0.70 and 9.71 ± 0.80 versus 8.56 ± 0.62 for MPV; 14.48 ± 1.29 and 14.98 ± 1.60 versus 12.86 ± 1.13 for PDW respectively). The MPV and PDW increased as the disease progressed. In the mild and severe ED groups, a significant inverse correlation was detected between the mean values of IIEF‐5 score and PDW. Furthermore, in the receiver operating characteristic curve analysis, the area under the curve of the MPV and PDW to predict severe ED was 0.818 and 0.848 respectively. Our study establishes a dose‐dependent association between the PDW and ED. Therefore, the PDW can serve as a potential marker for predicting the severity of ED.